Managerial economics : text, problems, and short cases - Seo, K. K.; Winger, Bernard J.; Spencer, Milton H. (Homewood, Ill. : R. D. Irwin, 1979)
Like previous editions, this fifth edition is aimed primarily at intermediate-level undergraduate and first-year graduate students in economics and business administration who require integrated training in managerial economics.
Fourth ed. (1975) by M. H. Spencer, K. K. Seo, and M. G. Simkin.
Includes bibliographical references and index.
ne 23/01/2019
Loans
Keywords: Managerial economics; Industrial management; Decision making